A Checklist of Angiospermic Flora of Tinjure-Milke-Jaljale, Eastern Nepal - Limbu, Dilkumar; Koirala, Madan; Shang, Zhanhuan (Nepal Journal of Science and Technology, 2013)
Tinjure–Milke–Jaljale (TMJ) area, the largest Rhododendron arboreum forest in the world, an emerging tourist area and located North-East part of Nepal. A total of 326 species belonging to 83 families and 219 genera of angiospermic plants have been documented from this area. The largest families are Ericaceae (36 species) and Asteraceae (22 genera). Similarly, the largest and dominant genus was Rhododendron (26 species) in the area. There were 178 herbs, 67 shrubs, 62 trees, 15 climbers and other 4 species of sub-alpine and temperate plants. The paper has attempted to list the plants with their habits and habitats. Nepal Journal of Science and Technology Vol. 13, No. 2 (2012) 87-96 DOI: http://dx.doi.org/10.3126/njst.v13i2.7719